Estrategias de asesoría y su influencia en el autocuidado de pacientes con diabetes que acuden al centro de salud 12 de octubre de Guayaquil durante el primer semestre del 2018. - Hidalgo Sanchez, Genesis (2018)
Globally, diabetes mellitus is considered to be the disease with the highest increase in deaths year after year, currently becoming the fourth cause of death, which is why it is considered a public health problem as a priority. The problem in this research work is based on the self-care of the diabetic patient. The objective of this research is to establish how counseling strategies influence the self-care of patients with diabetes who come to the Health Center October 12, Guayaquil. This study is descriptive and transversal quantitative. The techniques used are direct observation and surveys carried out on patients. The universe investigated is 86 diabetic patients. Conclusions.- Counseling strategies such as healthy eating, permanent physical activity, personal foot care, adherence to medical treatment, mutual or peer support, training for informal caregivers and telecuidado successfully influence the self-care of patients with diabetes. It is proposed to develop a guide that incorporates the innovative strategies that were manifested in the results.